Foundations - Shopware Productions; NAH 8 Production Group (New Jersey : Shopware, 2004)
This program explains the three types of foundations, which is basement foundation, crawl space foundation, and slab-on-grade-and uses a full basement foundation in a seasonal climate to illustrate basic techniques and concerns, including the use of footings, building forms, load-bearing values of the soil, and methods for pouring and curing concrete
Title from title screen
Executive producer, Chris Scherer
Keywords: Building trades -- Vocational guidance; Construction industry -- Vocational guidance; Foundations